Influences on the transport and establishment of exotic bird species: an analysis of the parrots (Psittaciformes) of the world - Phillip Cassey; Tim M. Blackburn; Gareth J. Russell; Kate E. Jones; Julie L. Lockwood (Global Change Biology, 2004)
Most studies of exotic species invasions only consider the factors that affect the establishment of populations following release, yet this is only one step on the invasion pathway. Different factors are likely to influence which species are transported and released. Here, we examine the influence of species traits on the successful transition of species through several stages in the introduction pathway (transport, release, and establishment), using parrots (Aves: Psittaciformes) as a model system. We use a species‐level supertree of parrots to test for phylogenetic auto‐correlation in the introduction process. Our analyses find that different sets of variables are related to the probability that a species enters each stage on the invasion pathway. The availability of individuals for transport and release seems to be most important for passage through these stages, but has no obvious effect on establishment following release. Rather, establishment success is higher for sedentary species, and species with broad diets.